2023
DOI: 10.3389/fpsyt.2023.1168516
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a diagnostic model and molecular subtypes of major depressive disorder based on endoplasmic reticulum stress-related genes

Abstract: SubjectMajor depressive disorder (MDD) negatively affects patients’ behaviours and daily lives. Due to the high heterogeneity and complex pathological features of MDD, its diagnosis remains challenging. Evidence suggests that endoplasmic reticulum stress (ERS) is involved in the pathogenesis of MDD; however, relevant diagnostic markers have not been well studied. This study aimed to screen for ERS genes with potential diagnostic value in MDD.MethodsGene expression data on MDD samples were downloaded from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
1
0
2
Order By: Relevance
“…The increase in eosinophils may be related to the inflammation and allergic characteristics of AD because they typically participate in allergic reactions and tissue inflammation(Naito & Kumanogoh, 2023). Interestingly, research has also found significant immune infiltration in MDD(S. Huang, Li, Shen, Liang, & Li, 2023). These findings provide a foundation and reference for future exploration of the association between AD and MDD.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in eosinophils may be related to the inflammation and allergic characteristics of AD because they typically participate in allergic reactions and tissue inflammation(Naito & Kumanogoh, 2023). Interestingly, research has also found significant immune infiltration in MDD(S. Huang, Li, Shen, Liang, & Li, 2023). These findings provide a foundation and reference for future exploration of the association between AD and MDD.…”
Section: Discussionmentioning
confidence: 98%
“…Следующей потенциальной группой биомаркеров для диагностики депрессии являются продукты синтеза генов KCNE1, PDIA4, STAU1, TMED4, MGST1, RCN1 и SHC1, связанных со стрессом эндоплазматического ретикулума (англ. endoplasmic reticulum stress; ERS) [17]. Представленные выше гены необходимы для нормального функционирования органеллы, так KCNE1 отвечает за формирование K + -каналов и формирование мембранного потенциала, KCNE1 модулирует нейрофизиологические механизмы восстановления после стресса -оказывает терапевтический эффект при депрессии.…”
unclassified
“…Представленные выше гены необходимы для нормального функционирования органеллы, так KCNE1 отвечает за формирование K + -каналов и формирование мембранного потенциала, KCNE1 модулирует нейрофизиологические механизмы восстановления после стресса -оказывает терапевтический эффект при депрессии. В исследовании [17] уровень активности данного биомаркера значимо коррелировал с количеством CD4+ T-клеток памяти и макрофагов фенотипа M0. Также имеется связь между генетическими факторами и активацией иммунной системы, которая зачастую приводит к оксидативному стрессу, митохондриальной дисфункции, нейродегенерации, апоптозу нервных клеток [18].…”
unclassified